Name
Grade
School

Date
Questions20
Score

1

10-(10+8)=

2

-7+10(6-8)=

3

4+(2-5)=

4

-6+(9-3)=

5

7+(7-5)=

6

-9+(9-4)=

7

-8+3(5-6)=

8

-4+3(2-5)=

9

5-(-7-5)=

10

-3+10(2-2)=

11

5-(4+9)=

12

9-(10+7)=

13

2-(-2-6)=

14

-10+(3-5)=

15

4-(-8-3)=

16

-1+(3-4)=

17

7-(10+5)=

18

-3+(6-7)=

19

-1+(3-3)=

20

6-(-7-8)=

Answers Key

Show All Workout

1

10-(10+8)=-8

Solution

The given Expression = 10-(10+8)

= 10-(18)

= 10-18

= -8

∴ 10-(10+8) = -8

= 10-(18)

= 10-18

= -8

∴ 10-(10+8) = -8

2

-7+10(6-8)=-27

Solution

The given Expression = -7+10(6-8)

= -7+10(-2)

= -7-20

= -27

∴ -7+10(6-8) = -27

= -7+10(-2)

= -7-20

= -27

∴ -7+10(6-8) = -27

3

4+(2-5)=1

Solution

The given Expression = 4+(2-5)

= 4+(-3)

= 4-3

= 1

∴ 4+(2-5) = 1

= 4+(-3)

= 4-3

= 1

∴ 4+(2-5) = 1

4

-6+(9-3)=0

Solution

The given Expression = -6+(9-3)

= -6+(6)

= -6+6

= 0

∴ -6+(9-3) = 0

= -6+(6)

= -6+6

= 0

∴ -6+(9-3) = 0

5

7+(7-5)=9

Solution

The given Expression = 7+(7-5)

= 7+(2)

= 7+2

= 9

∴ 7+(7-5) = 9

= 7+(2)

= 7+2

= 9

∴ 7+(7-5) = 9

6

-9+(9-4)=-4

Solution

The given Expression = -9+(9-4)

= -9+(5)

= -9+5

= -4

∴ -9+(9-4) = -4

= -9+(5)

= -9+5

= -4

∴ -9+(9-4) = -4

7

-8+3(5-6)=-11

Solution

The given Expression = -8+3(5-6)

= -8+3(-1)

= -8-3

= -11

∴ -8+3(5-6) = -11

= -8+3(-1)

= -8-3

= -11

∴ -8+3(5-6) = -11

8

-4+3(2-5)=-13

Solution

The given Expression = -4+3(2-5)

= -4+3(-3)

= -4-9

= -13

∴ -4+3(2-5) = -13

= -4+3(-3)

= -4-9

= -13

∴ -4+3(2-5) = -13

9

5-(-7-5)=17

Solution

The given Expression = 5-(-7-5)

= 5-(-12)

= 5+12

= 17

∴ 5-(-7-5) = 17

= 5-(-12)

= 5+12

= 17

∴ 5-(-7-5) = 17

10

-3+10(2-2)=-3

Solution

The given Expression = -3+10(2-2)

= -3+10(0)

= -3+0

= -3

∴ -3+10(2-2) = -3

= -3+10(0)

= -3+0

= -3

∴ -3+10(2-2) = -3

11

5-(4+9)=-8

Solution

The given Expression = 5-(4+9)

= 5-(13)

= 5-13

= -8

∴ 5-(4+9) = -8

= 5-(13)

= 5-13

= -8

∴ 5-(4+9) = -8

12

9-(10+7)=-8

Solution

The given Expression = 9-(10+7)

= 9-(17)

= 9-17

= -8

∴ 9-(10+7) = -8

= 9-(17)

= 9-17

= -8

∴ 9-(10+7) = -8

13

2-(-2-6)=10

Solution

The given Expression = 2-(-2-6)

= 2-(-8)

= 2+8

= 10

∴ 2-(-2-6) = 10

= 2-(-8)

= 2+8

= 10

∴ 2-(-2-6) = 10

14

-10+(3-5)=-12

Solution

The given Expression = -10+(3-5)

= -10+(-2)

= -10-2

= -12

∴ -10+(3-5) = -12

= -10+(-2)

= -10-2

= -12

∴ -10+(3-5) = -12

15

4-(-8-3)=15

Solution

The given Expression = 4-(-8-3)

= 4-(-11)

= 4+11

= 15

∴ 4-(-8-3) = 15

= 4-(-11)

= 4+11

= 15

∴ 4-(-8-3) = 15

16

-1+(3-4)=-2

Solution

The given Expression = -1+(3-4)

= -1+(-1)

= -1-1

= -2

∴ -1+(3-4) = -2

= -1+(-1)

= -1-1

= -2

∴ -1+(3-4) = -2

17

7-(10+5)=-8

Solution

The given Expression = 7-(10+5)

= 7-(15)

= 7-15

= -8

∴ 7-(10+5) = -8

= 7-(15)

= 7-15

= -8

∴ 7-(10+5) = -8

18

-3+(6-7)=-4

Solution

The given Expression = -3+(6-7)

= -3+(-1)

= -3-1

= -4

∴ -3+(6-7) = -4

= -3+(-1)

= -3-1

= -4

∴ -3+(6-7) = -4

19

-1+(3-3)=-1

Solution

The given Expression = -1+(3-3)

= -1+(0)

= -1+0

= -1

∴ -1+(3-3) = -1

= -1+(0)

= -1+0

= -1

∴ -1+(3-3) = -1

20

6-(-7-8)=21

Solution

The given Expression = 6-(-7-8)

= 6-(-15)

= 6+15

= 21

∴ 6-(-7-8) = 21

= 6-(-15)

= 6+15

= 21

∴ 6-(-7-8) = 21

Loading...

Loading...

Loading...

Loading...

kuku

Hey! I'm kuku

I can answer you simple math queries!

Hey! I'm kuku

I can answer you simple math queries!

Question
KuKu's Answer